Integration and Interference in the Cerebral Hemispheres: Relations with Hemispheric Specialization - Grimshaw, Gina M. (Brain and cognition, 1998)
The two hemispheres of the brain often perform complementary computations and make unique contributions to task performance. This study examines the interaction of linguistic (left hemisphere) and prosodic (right hemisphere) information in speech processing. An individual differences approach is used in which interference between linguistic and prosodic processes in a Stroop-like task is compared between individuals who process the two dimensions in opposite hemispheres (complementary specialization) vs. those who process both dimensions in the same hemisphere (noncomplementary specialization). Complementarity was not related to interference in any way. This finding is consistent with the hypothesis of Chiarello and Maxfield (1996) that interference is equivalent between and within hemispheres when it arises in a response selection stage.